Pemberdayaan Masyarakat Dalam Pengelolaan Sampah Di Kecamatan Kaimana Kabupaten Kaimana Provinsi Papua Barat - Sylvia Widy Syaharani Ufnia; Hendrayanti Hendrayanti (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2023)
Community empowerment in waste management is something that must be considered in the environment because one of the factors that influences the safety and comfort of community life is waste. The critical role of the government in empowering the community in waste management is to create a comfortable and clean community environment and realize community protection functions carried out by the government. Purpose: to find out and describe how community empowerment runs in waste management in Kaimana District, Kaimana Regency, West Papua Province. Method: In the qualitative approach, the data collection techniques are observation and documentary. Technical data analysis includes taking data, structuring and sorting out important ones, and drawing conclusions. Result: This study shows that Community Empowerment in Waste Management in Kaimana District, Kaimana Regency, West Papua Province, has been running well. It's just that there are still several obstacles that the Kaimana Regency Environmental Office must swiftly overcome. Conclusion: Community empowerment in Kaimana Regency has been going well; it's just that the Environmental Office still faces some obstacles with various efforts arranged.